A Tripartite Neurocognitive Model of Internet Gaming Disorder - Wei, Lei; Zhang, Shuyue; Turel, Ofir; Bechara, Antoine; He, Qinghua (Frontiers in Psychiatry, 2017)
Playing Internet games has emerged as a growing in prevalence leisure activity. In some cases, excess gaming can lead to addiction-like symptoms and aversive outcomes that may be seen by some as manifestations of a behavioral addiction. Even though agreement regarding the pahtologizing of excessive video gaming is not yet achieved and perhaps because the field requires more research, many works have examined the antecedents and outcomes of what is termed Internet Gaming Disorder (IGD). In this article, we aim at summarizing perspectives and findings related to the neurocognitive processes that may underlie IGD, and map such findings onto the triadic-system that governs behavior and decision making, the deficits in which have been shown to be associated with many addictive disorders. This tripartite system model includes the following three brain systems: (1) the impulsive system, which often mediates fast, automatic, unconscious, and habitual behaviors; (2) the reflective system, which mediates deliberating planning, predicting future outcomes of selected behaviors and exerting inhibitory control; and (3) the interoceptive-awareness system, which generates a state of craving through the translation of somatic signals into a subjective state of drive. We suggest that IGD formation and maintenance can be associated with (1) a hyperactive 'impulsive' system; (2) a hypoactive 'reflective' system, as exacerbated by (3) an interoceptive-awareness system that potentiates the activity of the impulsive system, and/or hijacks the goal-driven cognitive resources needed for the normal operation of the reflective system. Based on this review, we propose ways to improve the therapy and treatment of IGD and reduce the risk of relapse among recovering IGD populations.